Persona, Shadow dan Kepercayaan diri berhijab Remaja Putri dalam Kepribadian Jung - Ahad Hadi Setiawan; Doni Sastrawan; M. Wisnu Khumaedi; Hernisawati Hernisawati (Bulletin of Counseling and Psychotherapy, 2022)
We all have certain styles of behavior and ways of relating to other people. Some of us are ordinary types, others are careless. The purpose of this study is to analyze the personality constructs according to Carl Gustav Jung, namely Persona and Shadow, the problem formulation is seen based on the personality of white Muslim teenagers who wear hijab, whether as an identity or just a trend. Some of us prefer to do our own work, others are more social. The method in this research is literature study sourced from journals, books, and other sources. Some of us are followers, others are leaders. Some of us appear immune to the attacks of others, while others avoid social initiatives for fear of disappointment. When a pattern of behavior becomes so inflexible or maladaptive that it causes significant personal impairment or interferes with social and occupational functioning, it may be diagnosed as a personality disorder.